Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1016/j.atmosres.2008.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thunderstorm indices from ECMWF analyses, lightning data and severe storm reports

Abstract: This study describes the environmental atmospheric characteristics in the vicinity of different types of severe convective storms in Europe during the warm seasons in 2006 and 2007. 3406 severe weather events from the European Severe Weather Database ESWD were investigated to get information about different types of severe local storms, such as significant or weak tornadoes, large hail, damaging winds, and heavy precipitation. These data were combined with EUCLID (European Cooperation for Lightning Detection) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 40 publications
(58 reference statements)
5
79
1
3
Order By: Relevance
“…The highest values of SRH 03 are in EF2 soundings, as is also commented on the above‐mentioned article and in Kaltenböck et al . (). Four of the five EF2 soundings of our database surpassed an SRH 03 of 180 m 2 s −2 (not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest values of SRH 03 are in EF2 soundings, as is also commented on the above‐mentioned article and in Kaltenböck et al . (). Four of the five EF2 soundings of our database surpassed an SRH 03 of 180 m 2 s −2 (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…One additional parameter relevant in previous studies was also included: SBCAPE (e.g. Kaltenböck et al, ; Taszarek and Kolendowicz, ). All of them are listed and referenced in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Steiger et al (2007) found that a total lightning hole was associated with an intense, non-tornadic supercell; whereas none of the supercells exhibited a lightning hole in their observations over Dallas-Fort Worth, Texas. Kaltenböck et al (2009) also have reported more CG lightning during days with severe weather, especially with hail, wind and precipitation events from organized and clustered thunderstorm systems.…”
Section: Introductionmentioning
confidence: 94%
“…Nowadays, high-resolution models are resolving features such as synoptic forcing and local influences like orography and convergence zones which are predominant for thunderstorm initiation (Kaltenb€ ock et al 2009). Moreover, the need for proper soil moisture representation is well understood.…”
Section: Introductionmentioning
confidence: 99%